Long Term Control of Scabies Fifteen Years after an Intensive Treatment Programme. - Michael Marks; Betty Taotao-Wini; Lorraine Satorara; Daniel Engelman; Titus Nasi; David C Mabey; Andrew C Steer (PLoS Neglected Tropical Diseases)
Introduction Scabies is a major public health problem in the Pacific and is associated with an increased risk of bacterial skin infections, glomerulonephritis and rheumatic fever. Mass drug administration with ivermectin is a promising strategy for the control of scabies. Mass treatment with ivermectin followed by active case finding was conducted in five communities in the Solomon Islands between 1997 and 2000 and resulted in a significant reduction in the prevalence of both scabies and bacterial skin infections. Methods We conducted a prospective follow-up study of the communities where the original scabies control programme had been undertaken. All residents underwent a standardised examination for the detection of scabies and impetigo. Results Three hundred and thirty eight residents were examined, representing 69% of the total population of the five communities. Only 1 case of scabies was found, in an adult who had recently returned from the mainland. The prevalence of active impetigo was 8.8% overall and 12.4% in children aged 12 years or less. Discussion We found an extremely low prevalence of scabies 15 years after the cessation of a scabies control programme. The prevalence of impetigo had also declined further since the end of the control programme. Our results suggest that a combination of mass treatment with ivermectin and intensive active case finding may result in long term control of scabies. Larger scale studies and integration with other neglected tropical disease control programmes should be priorities for scabies control efforts.